Analysis and Simulation of SEIR Mathematical Model of Stunting Case in Indonesia - Winarni, Ambar; Sofiyati, Noor; Rudatiningtyas, Ulfa Fadilla (Universitas Wiralodra, 2024)
Stunting is one of the focuses of the target for improving nutrition in the world until 2025. The government of Indonesia targets the prevalence of stunting to decrease to 14% in 2024. There are some factor affect stunting, some of them are sanitation, health care and parenting of child. In this research, we constructed a SEIR mathematical model of stunting case in Indonesia. There are four compartements in this model : the population of newborn are likely to be exposed to stunting (S), the population of children were having an early symptom stunting (E), the population of affected child stunting permanent (I) and the population of children showing symptom stunting but no caught stunting (free stunting) (R). The disease free and endemic equilibrium point are the equilibrium of the formed model. The local stability of equilibrium points have been analyzed, determined the basic reproduction number, and conducted a sensitivity analysis. If then is asymptotically stable If then is asymptotically stable. Sensitivity analysis revealed that the parameters and significantly contribute to the increase in the basic reproduction number . It means that the good sanitation, good healthcare, good parenting of child and decrease the rate of transmission indirectly from the person affected stunting are the most important thing to reduce the rate of stunting in Indonesia.